KEPEMIMPINAN PENDIDIKAN DALAM AL-QURAN (Studi Pustaka Kisah-kisah dalam al-Quran) - Rosidin, Rosidin (STAI Ma'had Aly Al-Hikam Malang, 2017)
Al-Quran is the main source of Islamic educational concept. The Quranic text is constant, while its contextualization and its implementation are dynamic throughout Muslim history. Therefore its verses could be interpreted as the answer to the problems of Islamic education nowadays. One of the Educational problems within Islamic education is the problem of leadership. At least, there are seven stories of leadership within the Quran. The lesson learned from these stories of leadership can be concluded as follows; there are four leadership competencies, i.e: moral, professional, social, and intellectual competencies. These competencies are equivalent to the prophetic qualities: Siddiq, Amanah, Tabligh, and Fatanah.